Sistem Pakar Online Pendeteksi Penyakit Tanaman Adenium Dengan Metode Prototyping - Syahriani Syahriani; Dimas Aryo Dirgantoro (JURNAL TEKNIK KOMPUTER, 2019)
- This adenium plant is a plant that began to demand by many hobbyist plants because plants have unique characteristics Adenium. In addition adenium treatment is also very easy, but adenium plants are also susceptible to pest disease, so it becomes a disease that can make this adenium plant damaged or dead. The lack of expert on adenium plant diseases causes the hobbyists to find it difficult to recognize the symptoms and ways to cure when the plant is infected with the disease. This expert system is made to facilitate the hobbyists in coping with adenium plant diseases. The method used in this expert system is forward chaining, because the Forward Chaining method is a suitable method for the control and forecasting of adenium plant diseases. This expert system application will display the question about the symptoms of adenium plant disease that attack and can be found the solution by experts who have experienced in their field, after that the system will display the results of the disease that attacks his adenium plants along with the characteristics and how to cope with the disease.  Keywords: Adenium, Expert System, Forward Chaining